Isolation of Flavonoid Compounds from Salam (Syzygium polyantha Wight) Leaves - Pasaribu, Albert; Simamora, Monojaya; Lenny, Sovia (Journal of Chemical Natural Resources, 2021)
Isolation of flavonoid compounds from Salam (Syzygium polyantha Wight) leaves has been done by maceration technique with methanol solvent. Methanol extract obtained was evaporated and dissolved with ethyl acetate. The solution was then concentrated and evaporated. The ethyl acetate fraction was dissolved with methanol and partitioned with n-hexane solvent. The methanol layer was evaporated and then tested with Benedict’s reagent and then acidified with HCl 6% while heated. It was then extracted partition with chloroform. The chloroform layer was separated using Column Chromatography with silica gel as the stationary phase and n-hexane: ethyl acetate 90:10, 80:20, 70:30, and 60:40 v/v, respectively as the mobile phase. The pure compound was paste, brownish red, mass = 8.5 mg, and Rf=0.60. It was a positive reaction with flavonoid compound reagents. The compound was further identified by using UV-Visible, FT-IR, and 1H-NMR spectroscopy. Spectroscopy data obtained indicated that the compound is a flavonoid.